In situ observation of the water-sediment interface in combined sewers, using endoscopy - Oms, C.; Gromaire, M.C.; Chebbo, G. (3rd International Conference on Sewer Processes and Networks (3rd SPN), 2002)
A new method for water-sediment interface observation has been designed. This system is based on a small diameter endoscope protected by a graduated plastic tube. It makes it possible to visualise in a non-destructive manner the sediments and the water-sediment interface. The endoscope was used to investigate Le Marais catchment (Paris): an immobile organic layer was observed at the water-sediment interface. This layer appears in pools of gross bed sediment, at the upstream of collectors, in zones where, velocity is slow and where bed shear stress is less than 0.03 N/m(2).